Porcine circovirus type 2 detection in in vitro produced porcine blastocysts after virus sperm exposure. (5th October 2015) - Galeati, Giovanna; Zannoni, Augusta; Spinaci, Marcella; Bucci, Diego; Ostanello, Fabio; Panarese, Serena; Tamanini, Carlo; Sarli, Giuseppe
Abstract: This study was aimed at assessing the capability of semen experimentally infected with porcine circovirus type 2 (PCV2) to produce porcine blastocysts PCR positive for PCV2. Embryos were obtained from in vitro maturation (IVM) and in vitro fertilization (IVF) of porcine oocytes or by parthenogenesis. Sperm suspension was exposed to PCV2b and utilized for IVF. PCV2 spiked semen did not reveal any reduction in sperm viability or motility but its ability to produce infected blastocysts was irrelevant as only one out of 15 blastocysts obtained by IVF were PCV2b; however two blastocysts were PCV2a positive. Furthermore, the presence of PCV2 was demonstrated also in embryos obtained by parthenogenesis (one out of 17 was PCV2b and one PCV2a positive). Even if PCV2 firmly attaches to the surface of spermatozoa, experimentally spiked sperm were not effective in infecting oocytes during IVF and in producing PCR positive embryos. The infected blastocysts we obtained derived most probably from infected oocytes recovered at the abattoir.